Economic Policies and their Influence on Livestock Market Dynamics - Mukasa, Jennifer (International Journal of Livestock Policy, 2024)
Purpose: The general objective of the study was to explore the economic policies and their influence on livestock market dynamics. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to economic policies and their influence on livestock market dynamics. Preliminary empirical review revealed that fiscal policies, such as subsidies and tax incentives, play a crucial role in reducing production costs and stabilizing market supply. Likewise, monetary policies, including interest rate adjustments, influence investment and innovation within the sector. Trade policies, such as tariffs and free trade agreements, affect market competitiveness and access to international markets. Regulatory policies concerning animal health and environmental protection ensure product quality and consumer confidence. The study emphasizes the need for balanced and well-designed policies across all these areas to support the sustainable growth of the livestock industry. Unique Contribution to Theory, Practice and Policy: Keynesian Economic Theory, Neoclassical Economic Theory and Institutional Economic Theory may be used to anchor future studies on economic policies and their influence on livestock market dynamics. The study significantly advances theoretical understanding by elucidating the intricate relationship between economic policies and livestock market dynamics. It recommends further exploration into the interplay of fiscal, monetary, trade, and regulatory policies to develop comprehensive models predicting market behavior accurately. Practically, the study advises livestock producers to adopt adaptive management practices, staying informed about policy changes and implementing flexible business strategies. Industry associations are urged to disseminate policy information and support farmers in navigating shifts. From a policy standpoint, coherence, targeting, and responsiveness to sectoral needs are underscored, advocating for a holistic approach to policy design. Fiscal policies should support short-term stability and long-term sustainability, targeting critical areas like feed costs and infrastructure. Monetary policies should balance investment stimulation with inflation control, while trade and regulatory policies should negotiate balanced agreements and stringent standards to ensure competitiveness and safety in the global market.